Role of traditional Chinese medicine monomers in cerebral ischemia/reperfusion injury:a review of the mechanism - Zheng, Ting; Jiang, Taotao; Huang, Zilong; Ma, Hongxiang; Wang, Manxia (Frontiers in Pharmacology, 2023)
Ischemia/reperfusion (I/R) injury is a pathological process wherein reperfusion of an ischemic organ or tissue exacerbates the injury, posing a significant health threat and economic burden to patients and their families. I/R triggers a multitude of physiological and pathological events, such as inflammatory responses, oxidative stress, neuronal cell death, and disruption of the blood-brain barrier (BBB). Hence, the development of effective therapeutic strategies targeting the pathological processes resulting from I/R is crucial for the rehabilitation and long-term enhancement of the quality of life in patients with cerebral ischemia reperfusion injury (CIRI). Traditional Chinese medicine (TCM) monomers refer to bioactive compounds extracted from Chinese herbal medicines, possessing anti-inflammatory and antioxidative effects, and the ability to modulate programmed cell death (PCD). TCM monomers have emerged as promising candidates for the treatment of CIRI and its subsequent complications. Preclinical studies have demonstrated that TCM monomers can enhance the recovery of neurological function following CIRI by mitigating oxidative stress, suppressing inflammatory responses, reducing neuronal cell death and functional impairment, as well as minimizing cerebral infarction volume. The neuroprotective effects of TCM monomers on CIRI have been extensively investigated, and a comprehensive understanding of their mechanisms can pave the way for novel approaches to I/R treatment. This review aims to summarize the protective effects and potential clinical value of TCM monomers in CIRI, with a focus on their role in modulating oxidative stress, inflammation, neuronal cell death, glutamate excitotoxicity, Ca2+ overload, as well as promoting blood-brain barrier repairment and angiogenesis. The main objective is to underscore the significant contribution of Chinese herbal monomers in alleviating cerebral ischemic injury.